Impacto de la polinización en la formación de frutas y rendimiento del tomate de árbol Solanum betaceum. Cav - Rosado Fajardo, Mayerlin Doménica (2024)
The tree tomato or tamarillo (Solanum betaceum) plays a vital role in agriculture and the economy due to its nutritional and commercial value. However, lack of pollination has become a major problem that affects its performance. This study highlights the importance of understanding the role of pollination in fruit formation to ensure crop sustainability. The problem identified was a shortage of pollinators due to unpredictable weather conditions and unsustainable agricultural practices, resulting in significant decreases in tree tomato yields. The objectives of the study include determining the effects of pollination on crops, identifying the main pollinators and analyzing their impact on plant performance. The results showed that crop yields increased significantly after the introduction of certain pollinators, highlighting their direct impact on fruit quality and economic value. The importance of pollinator diversity to improve the genetic composition and quality of fruit. It concludes with the need to recognize the importance of pollination to increase productivity and provides recommendations to optimize pollination conditions and maximize yields in tree tomato crops.